2019
DOI: 10.1051/e3sconf/20198600026
|View full text |Cite
|
Sign up to set email alerts
|

Influence of environmental factors on retention of extensive green roofs with different substrate composition

Abstract: Increasing recognition is being given to the adaption of green roofs in urban areas to enhance the local ecosystem. Green roofs may bring several benefits to urban areas including flood mitigation Analysis of environmental factors affecting the outflow of green roofs is the subject of many studies. The work assessed how environmental factors moisture of structural layers and antecedent dry weather period influence the retention on two types of green roof substrates. The monitoring of environmental factors and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Baryła et al found that ADP as well as antecedent volumetric moisture content are the parameters that determine the preceding level of moisture in the substrate. They found that the relationship between these two parameters was moderately negative, whereas ADP did not exhibit statistically significant correlation with retention [Baryła et al, 2019]. It should be emphasized that during the investigations described in the current paper, the lengths of periods elapsed from the previous total saturation PSTS obtained in the case of 6 rainfalls were relatively similar.…”
Section: Resultsmentioning
confidence: 48%
“…Baryła et al found that ADP as well as antecedent volumetric moisture content are the parameters that determine the preceding level of moisture in the substrate. They found that the relationship between these two parameters was moderately negative, whereas ADP did not exhibit statistically significant correlation with retention [Baryła et al, 2019]. It should be emphasized that during the investigations described in the current paper, the lengths of periods elapsed from the previous total saturation PSTS obtained in the case of 6 rainfalls were relatively similar.…”
Section: Resultsmentioning
confidence: 48%
“…Schultz et al [39] reported that both the ADWP and the precipitation depth influence the amount of water retained within green roof during individual rain event. Baryla et al [40] found that both ADWP and the antecedent volumetric moisture content are the parameters that influence the preceding moisture level in the substrate and thus the retention depth. On the other hand, however, they reported not statistically significant correlation between ADWP and retention, but their research was conducted in natural conditions and they have taken into account all precipitations having diversified depths and intensities [40].…”
Section: Resultsmentioning
confidence: 99%
“…Baryla et al [40] found that both ADWP and the antecedent volumetric moisture content are the parameters that influence the preceding moisture level in the substrate and thus the retention depth. On the other hand, however, they reported not statistically significant correlation between ADWP and retention, but their research was conducted in natural conditions and they have taken into account all precipitations having diversified depths and intensities [40]. In another publication Baryla [41] found that the volume of precipitation, the initial moisture substrate, and ADWP have a significant effect on green roof retention.…”
Section: Resultsmentioning
confidence: 99%
“…If the vegetated roof reaches its saturation level at a given time and under specific internal conditions, other factor's contribution may be significant (Stovin et al, 2015). Nevertheless, the effect of rainfall depth on retention would compensate for the other factors when the disparity between the two is substantial (Baryła et al, 2019).…”
Section: Rainfall Depth and Intensitymentioning
confidence: 99%